Molecular dynamic simulations on TKX-50/HMX cocrystal. Issue 11 (24th January 2017) - Xiong, Shuling; Chen, Shusen; Jin, Shaohua; Zhang, Zhe; Zhang, Yan; Li, Lijie
Abstract : TKX-50/HMX cocrystal model was established and calculated using PCFF force field by molecular dynamics simulations. Abstract : Dihydroxylammonium 5, 5′-bistetrazole-1, 1′-diolate (TKX-50) is a newly synthesized explosive with excellent comprehensive properties. Cyclotetramethylenetetranitramine (HMX) is currently one of the highest energy explosives used around the world. TKX-50/HMX cocrystal can improve the defects of TKX-50 and HMX and vastly expand their application scope. TKX-50 and HMX supercell structures and TKX-50/HMX cocrystal structures were established based on their crystal cell parameters and the formation mechanism of the cocrystals, respectively. The binding energy, radial distribution function (RDF), X-ray powder diffraction (XRD), cohesive energy density (CED) and mechanical properties were simulated based on the equilibrium structures of models via molecular dynamics (MD) simulations. The calculated results indicate that the TKX-50/HMX cocrystal forms as a new structure under the intermolecular forces, and the cocrystal structures of TKX-50 substituted by HMX on its slow-growing facets are more stable. Moreover, the cocrystal structure has greatly improved the high sensitivity defect of HMX and the mechanical properties of TKX-50 and HMX; thus the cocrystal will be more likely to be used widely in the energetic materials field.